Finance and Me (FinME) - a digital learning tool / Carolin Ann Enchas ... [et al.] - Enchas, Carolin Ann; Abu Talib, Shafinaz Lyana; Razali, Fatin Adilah; Ibrahim, Norizuandi (2021)
Creating an engaging learning environment is challenging when it comes to online learning. Teaching the Fundamentals of Finance via an online platform to finance and non-finance students can be a challenging task as they are distanced from their peers and lecturers. This increases the chance of being disengaged and demotivated from the lesson. The lecturers' factual presentations are frequently dull and boring. Therefore, with the help of technology, FinME, a digitalized educational finance game was invented to address the issue. Students are more motivated by the added game element, as well as the excitement of thinking that they are playing instead of learning. This game can be used as a support tool in teaching the Fundamentals of Finance course and helps to boost the student's financial knowledge for better understanding and application. Students are given the opportunity to play the game on their gadgets (phones or laptops). In this game, the students are given a mission to complete and along the way they need to solve several tasks that are related to the course, as well as encounter an unexpected event that will deviate them from completing their mission. Although games cannot replace the entire teaching process, they can be integrated into the delivery of the Fundamentals of Finance course to enhance the overall learning experience.